Access control to table rows using hierarchy of authority - Коломыцев, Михаил Владимирович; Носок, Светлана Александровна; Мазуренко, Анастасия Евгеньевна (Ukrainian Information Security Research Journal, 2016)
The article is devoted to the actual problem of the information protection in databases. Applications for databases access in the enterprise information system require access control by programming of access mechanism at the level of the database table rows (Row Level Security) to ensure the flexibility of security policy for data access. The existing approaches require the creation of additional columns in tables and program objects that define the mechanisms for rows filtering. The article proposes another approach where the rules of the granting permissions are in a separate table. The method is based on access restricting to data in specific rows in the table for reading, modifying and deleting. The method uses structural and job hierarchy of users, database objects and programming templates of operations for access control in different DBMS. The proposed method is implemented as special tables, triggers, views and user-defined functions for the database management system (DBMS) MS SQL Server. The goal is to develop a method for access control to table rows based on structural and job hierarchy of users.